Macrophage Depletion Mitigates Platelet Aggregate Formation in Splenic Marginal Zone and Alleviates LPS-Associated Thrombocytopenia in Rats - Li, Ying; Ryan, Johannah; Xu, Fei; Vostal, Jaroslav G. (Frontiers in Medicine, 2019)
Sepsis is often accompanied with thrombocytopenia partly due to platelet sequestration in the lung and liver. The spleen can store up to one-third of circulating platelets and can also significantly affect platelet transfusion outcomes by accumulating platelets. However, in sepsis, it is not clear whether there are platelet changes in the spleen which could contribute to sepsis-associated thrombocytopenia and influence platelet transfusion outcomes. By using confocal microscopy, we examined endogenous rat platelets and infused human platelets in the spleen of severe combined immune deficient Rag2 KO rats which were injected intraperitoneally with lipopolysaccharide (LPS). LPS-injected Rag2 KO rats developed sepsis as indicated by increased TNFa, IL-6, IL-1b and IL-10 levels and thrombocytopenia. Large platelet aggregates were observed in the spleen with majority located in the marginal zone and closely associated with CD169+ macrophages. Depletion of macrophages by clodrosome resulted in reduction of LPS-induced cytokine generation and alleviated LPS-induced thrombocytopenia. Macrophage depletion also markedly diminished large platelet aggregate formation in the splenic marginal zone but had less effect on those in red pulp. Infusion of human platelets into LPS-injected rats failed to raise platelet counts in the peripheral blood. In LPS-injected rat spleen, human platelets interacted with aggregated rat platelets in the marginal zone. In contrast, human platelets infused into control rats were located outside of splenic marginal zone. This study provides morphological evidence of platelet aggregates in the splenic marginal zone in sepsis which can interact with infused platelets and thus can contribute to platelet infusion refractoriness in sepsis. It indicates that macrophages play an important role in LPS-associated thrombocytopenia. It also suggests that CD169+ macrophages support platelet aggregate formation in the splenic marginal zone.